Assessing the Quality of Life and Functional Disability in Some Musculoskeletal Disorders - Abedi, Mohsen (Journal of Clinical Physiotherapy Research, 2019)
Introduction: Low back pain, knee disorders and rheumatoid arthritis are the most common musculoskeletal diseases in Iran and throughout the world. The studies conducted in the developed countries have shown that this disease has considerable effect on the functional abilities and quality of life of patients. There are a few studies about this issue in Iran. Therefore, this study aims to evaluate the effect of knee and low back pain on the functional disability and quality of life of patients resident in Tehran. Materials and Methods: 220 musculoskeletal disorders (knee and low back pain and rheumatoid arthritis) from one hospital in Tehran, Iran participated in the study. Persian versions of Arthritis Impact Measurement Scale 2-short form (AIMS2-SF) and Short form health survey (SF-12) were used to measure the functional disability and quality of life. AIMS2-SF questionnaire that has been designed exclusively for rheumatoid arthritis patients measures the functional disability of patients in five dimensions: physical (upper and lower limbs), symptoms, feelings and social condition. Results: mean age and education of patients in this study was 53(low back pain), 45 (knee pain), and 58 (RA) years old, respectively. 59% of subjects were women. Mean of physical dimensions, upper limbs, lower limbs, symptoms, feelings, and social conditions were 1.46, 1.32, 2.12, 3.65, 3.40, and 3.78 (of 10), respectively. The mean of eight dimensions of quality of life based on the SF-12 questionnaire was 43 to 64 (of 100). Conclusion: The results of this study showed that the quality of life and functional abilities of musculoskeletal disorders are influenced significantly by diseases. Based on this, the increasing of physical activity and the intensive physiotherapy programs result in improvement of quality of life in these diseases.